Revolutionizing Learning in the 21st Century: Development of Video Microlearning Anchored in TPACK - Fidhyallah, Nadya Fadillah; Aladawiya, Rabia; Zakiah, Rizka; Faslah, Roni; Sulistyowati, Raya; Susilowati, Nenden; Armayanti, Nelly (JTP - Jurnal Teknologi Pendidikan, 2024)
It is important to foster 21st-century skills in the context of modern education. However, integrating these skills into the curriculum remains challenging. This study addresses the gap by developing TPACK-based (Technological Pedagogical Content Knowledge) video microlearning towards relevant curriculum in Indonesia. The objective of this research is to create effective video microlearning content that aligns with the TPACK framework. Utilizing Thiagarajan's 4D model—define, design, develop, and disseminate—the study employed a research and development approach. Data were gathered through expert evaluations of media and content, and feedback from teachers and students. The sample included 10th-grade Marketing students at SMKN 12 Jakarta. The findings demonstrated a 95% feasibility rate for the media and a 92% success rate for the content, indicating high effectiveness and suitability for instructional purposes. Further testing with teachers and students yielded positive responses of 94% and 95%, respectively. These results highlight the significance of TPACK-based video microlearning as a valuable instructional tool, capable of enhancing 21st-century skills in students. The novelty of this research lies in its application of the TPACK framework to video microlearning, addressing the urgent need for innovative educational strategies.